Spatiotemporal gating of Stat nuclear influx by Drosophila Npas4 in collective cell migration. - Wu, J.W.; Wang, C.W.; Chen, R.Y.; Hung, L.Y.; Tsai, Y.C.; Chan, Y.T.; Chang, Y.C.; Jang, A.C. (Science advances, 2022)
Collective migration is important to embryonic development and cancer metastasis, but migratory and nonmigratory cell fate discrimination by differential activity of signal pathways remains elusive. In Drosophila oogenesis, Jak/Stat signaling patterns the epithelial cell fates in early egg chambers but later renders motility to clustered border cells. How Jak/Stat signal spatiotemporally switches static epithelia to motile cells is largely unknown. We report that a nuclear protein, Dysfusion, resides on the inner nuclear membrane and interacts with importin ?/? and Nup153 to modulate Jak/Stat signal by attenuating Stat nuclear import. Dysfusion is ubiquitously expressed in oogenesis but specifically down-regulated in border cells when migrating. Increase of nuclear Stat by Dysfusion down-regulation triggers invasive cell behavior and maintains persistent motility. Mammalian homolog of Dysfusion (NPAS4) also negatively regulates the nuclear accumulation of STAT3 and cancer cell migration. Thus, our finding demonstrates that Dysfusion-dependent gating mechanism is conserved and may serve as a therapeutic target for Stat-mediated cancer metastasis.